2022
DOI: 10.1037/cou0000572
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of change in chronic depression: Differences in self-criticism and somatic symptoms between users of antidepressants and nonmedicated patients.

Abstract: Objective: Depression is typically seen as composed of several factors (i.e., cognitive, affective, somatic) which may be targeted by different interventions (i.e., pharmacotherapy, psychotherapy, or combination treatment). Successfully targeting these factors may contribute to improved treatment response in depression. A previous study identified two subfactors on Beck Depression Inventory-II (BDI-II) in a sample of chronically depressed patients: (a) self-criticism and (b) somatic symptoms (sleep disturbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Foreign studies have found that female medical staff generally suffer from subjective physical discomfort and lower moods [21]. In addition, other studies have found that depressive symptoms occur more often in women than in men [22], the prevalence of depression among female physicians is about 1.5 times higher than that of men and the prevalence of severe depression is about eight times higher [23]. The results of domestic studies indicate that the mental health quality of female medical personnel is lower than that of men [24][25][26].…”
Section: Analysis Of the Influencing Factors On The Mental Health Of ...mentioning
confidence: 99%
“…Foreign studies have found that female medical staff generally suffer from subjective physical discomfort and lower moods [21]. In addition, other studies have found that depressive symptoms occur more often in women than in men [22], the prevalence of depression among female physicians is about 1.5 times higher than that of men and the prevalence of severe depression is about eight times higher [23]. The results of domestic studies indicate that the mental health quality of female medical personnel is lower than that of men [24][25][26].…”
Section: Analysis Of the Influencing Factors On The Mental Health Of ...mentioning
confidence: 99%
“…Many depressed patients use antidepressant medication (ADM) and chronically depressed patients often present for psychotherapy on a course of ADM [7, 8]. It is unclear how treatment with ADMs impacts long-term outcomes in depression, and it is difficult to predict how patients using ADM will respond during WL compared to nonmedicated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Few vegetative symptoms are considered part of the diagnostic routine; for example, fatigue, loss of appetite, and sleep [ 33 ]. Understanding the individual burden profile has been found to be crucial for targeted treatment, as patients with higher values in self-criticism respond better to psychotherapy than those with a somatic symptom profile [ 34 ]. As a result, in developing an item pool for daily mood tracking in e-mental health apps, somatic symptoms should be considered to a certain extent.…”
Section: Introductionmentioning
confidence: 99%